Facial trauma caused by firearm. Gunshot facial trauma - Rivadeneira Maldonado, Andrés (Revista Universidad de Guayaquil, 2013)
The constant evolution of firearms and the gradual increase in violence during riots, fights and assaults in our societyt, have resulted in a number of facial traumas due to these two variables listed above. Thus, this case illustrates the timely resolution of a case received in our nursing home, where a synchronized management of the group of physicians from the Plastic and Craniofacial Surgery Area of our institution is demonstrated. . As a result, we found that in this two- stage surgical procedure, the priority is given to the initial restoration and cleansing of the functional part of the area , sparing as much healthy tissue as possible, in the second stage we performed surgical placement of osteosynthesis and lateral rotation flap at nose level, to cover the projectile outlet , thus achieving facial harmony and a good degree of satisfaction by patients and their families
Keywords: facial trauma; firearm; Reconstruction; Lateral Flap; Comminuted Fracture